2010
DOI: 10.1038/mt.2010.26
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Translational Dual-regulated Oncolytic Herpes Simplex Virus Type 1 for Targeting Prostate Tumors

Abstract: The aim of this project was to demonstrate that an oncolytic herpes simplex virus type 1 (HSV-1) can replicate in a tissue- and tumor-specific fashion through both transcriptional (prostate-specific promoter, ARR(2)PB) and translational (5'-untranslated regions (5'UTRs) of rFGF-2) regulation of an essential viral gene, ICP27. We generated two recombinant viruses, ARR(2)PB-ICP27 (A27) and ARR(2)PB-5'UTR-ICP27 (AU27) and tested their efficacy and toxicity both in vitro and in vivo. The ARR(2)PB promoter caused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…was required for the function of the virus (Barker et al, 2003;Larson et al, 2015;Lee et al, 2010;Singh et al, 2012). For example, one study constructed an adenovirus in which gene E1a was under the control of the hTERT (human telomerase reverse transcriptase) promoter while the viral gene E1b was under the control of the HRE (hypoxia response element) promoter .…”
Section: Using Combinations Of Markers For a More Robust And Specificmentioning
confidence: 99%
“…was required for the function of the virus (Barker et al, 2003;Larson et al, 2015;Lee et al, 2010;Singh et al, 2012). For example, one study constructed an adenovirus in which gene E1a was under the control of the hTERT (human telomerase reverse transcriptase) promoter while the viral gene E1b was under the control of the HRE (hypoxia response element) promoter .…”
Section: Using Combinations Of Markers For a More Robust And Specificmentioning
confidence: 99%
“…8,24 In this regard, our laboratory has previously demonstrated that eIF4E is a good discriminatory factor between normal and cancer cells as eIF4E levels are substantially elevated in the latter. 4,15,20 eIF4E is the rate-limiting subunit of the eIF4F complex, which is comprised of eIF4E, the cap binding protein; eIF4A, an ATPase and RNA helicase; and eIF4G, a scaffolding protein. eIF4E is critical for initiating the process of translation by binding to the 5 0 -cap 7-methylguanosine (m7G) present on all nuclear transcribed mRNAs, 25 and together with the eIF4F complex, unwinds the excess secondary structures within the 5 0 UTR to facilitate the loading of the 40S ribosomal subunit to the mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of eIF4E levels in prostate cancer cell lines to those in nonmalignant prostate cells (Figure 1) revealed that eIF4E levels were higher in cancer cell lines, in agreement with what has been previously shown. 20 To establish that our lentiviral plasmids containing complex 5 0 UTRs are translated at a lower rate in nonmalignant cells, lentiviral transfer plasmids (FUGW, FU-ODC 149 -GW, FU-ODC 274 -GW and FU-FGF2-GW) were transfected into nonmalignant prostate cells. Expression of each plasmid was estimated through GFP protein expression and normalized to control FUGW plasmid.…”
Section: Discussionmentioning
confidence: 99%
“…A recent example provided by Lee and colleagues [105] not only demonstrates successful translational regulation in a RCOV but also shows how regulatory regimes can be designed which interact synergistically and produce greater oncolytic selectivity than would be possible with just a single regulatory constraint. The HSV-1 gene ICP27 is essential for viral replication [106].…”
Section: Translational Restrictionmentioning
confidence: 99%
“…The HSV-1 gene ICP27 is essential for viral replication [106]. Lee and colleagues [105] have engineered a recombinant HSV-1 in which the ICP27 gene was placed under both transcriptional and translational control. A modified promoter (designated ARR2PB) for the prostate-specific protein probasin [107] was used to drive expression of ICP27 in the recombinant HSV-1.…”
Section: Translational Restrictionmentioning
confidence: 99%